The NF‐κB binding site located in the proximal region of the TSLP promoter is critical for TSLP modulation in human intestinal epithelial cells. Issue 4 (11th February 2013) - Cultrone, Antonietta; de Wouters, Tomas; Lakhdari, Omar; Kelly, Denise; Mulder, Imke; Logan, Elizabeth; Lapaque, Nicolas; Doré, Joel; Blottière, Hervé M.
<x xml:space="preserve">Abstract</x> Thymic stromal lymphopoietin (TSLP) is constitutively secreted by intestinal epithelial cells. It regulates gut DCs, therefore, contributing to the maintenance of immune tolerance. In the present report, we describe the regulation of TSLP expression in intestinal epithelial cells and characterize the role of several NF‐κB binding sites present on the TSLP promoter. TSLP expression can be stimulated by different compounds through activation of p38, protein kinase A, and finally the NF‐κB pathway. We describe a new NF‐κB binding element located at position –0.37 kb of the promoter that is crucial for the NF‐κB‐dependent regulation of TSLP. We showed that mutation of this proximal NF‐κB site abrogates the IL‐1β‐mediated transcriptional activation of human TSLP in several epithelial cell lines. We also demonstrated that both p65 and p50 subunits are able to bind this new NF‐κB binding site. The present work provides new insight into epithelial cell‐specific TSLP regulation.